Erros de medicação no serviço de atendimento móvel de urgência: fatores potencialmente envolvidos segundo a percepção da equipe de enfermagem - Nara Rodrigues Pereira (2017)
In 2003, the Brazilian Ministry of Health established the Mobile Emergency Care Service (SAMU) as a part of the prehospital care within the Unified Health System (SUS). The SAMU,, the main component of the National Emergency Care Policy, has its origins based on both the Franco-German and the Anglo-American model, consisting of a central emergency medical regulation, basic support ambulances manned by nursing technicians and lifeguards drivers and advanced support units, having as a team a driver Lifeguard, a nurse and a doctor. The responsibility for medicines preparation and administration in SAMU belongs to nursing technicians and nurses according to the support type, basic or advanced, respectively. This function is extremely important and requires attention as it is the last barrier to prevent a medication error from reaching the patient. The occurrence of medication errors represents a quality problem in care, responsible for increasing monetary and social costs, generating suffering for the patient, their relatives and the professionals involved. The aim of the study was to identify factors with potential to cause medication errors in the SAMU system, as well as the frequency of errors. This is a cross-sectional census study, developed in the SAMU of the central-southern region of the state of Minas Gerais. We invited 140 nursing technicians and 28 nurses working in the service to participate in the study responding to a questionnaire that addressed sociodemographic characteristics, knowledge about medication errors and the experience of the error. Attendance records were analyzed to estimate frequency of errors in medications controlled by special prescriptions. The response rate was 68.5%. Most of the participants was female and had more than one workplace in the health area. The major difficulties with medications were nomenclature (47.8%), dosage (16.5%) and mode of dilution (11.3%). The lighting inside the vehicle was the most important negative environmental influence. Repetition of oral prescription via telemedicine and similarity between ampoules appeared as potential error determinants. The wrapping bag type, its routine conference and prescription by the name on the packaging were cited as important for safe use. Most reported not having seen errors, but the analysis of the records showed errors involving drugs controlled by special prescription in 4.5% of the visits, being those related to wrong medicine and wrong dose the most common. Although errors are preventable, few studies have investigated such events within mobile emergency services, making prevention actions difficult. The identification of the main factors potentially involved in the occurrence of these errors becomes crucial for the promotion of actions for the safety of the patient and the quality of care provided.